Independent Mental Health Advocacy: A Model of Social Work Advocacy?. Issue 3 (2nd July 2020) - Maylea, Christopher; Makregiorgos, Helen; Martin, Jennifer; Alvarez-Vasquez, Susan; Dale, Matthew; Hill, Nicholas; Johnson, Brendan; Thomas, Stuart; Weller, Penelope
ABSTRACT: Advocacy has received less attention in social work research than other aspects of social work practice. This paper draws attention to two tensions in social work advocacy; between worker-led advocacy and person-led advocacy, and between individual advocacy and system level advocacy. We argue that human-rights-based social workers must choose a person-led approach over a worker-led approach while advocating with both systems and individuals. This argument is made by drawing on findings of an evaluation of Independent Mental Health Advocacy (IMHA) in Victoria, Australia. It is shown that social work training had not prepared social workers for rights-based, person-led advocacy and that social workers in public mental health services were struggling to maintain the rights of people in their services even with assistance from IMHA. IMPLICATIONS Independent Mental Health Advocacy (IMHA) is a model of advocacy influenced by social work theory and delivered in part by social-work-trained advocates. Social work training is not preparing social workers for person-led, human-rights-based advocacy. Public mental health social workers are struggling to maintain the rights of people in mental health services even with the support of external advocacy services.